Answers

2014-09-07T18:15:03+05:30
(2/3)x-1/12=(3/2)x
[Now, take remainder of remainder of statement at L.H.S(Left Hand Side)
We get:
(8x-1)/12 = (3/2)x]

So,
(8x-1)/12 = (3/2)x
(Now, we will do cross multiplication)
2(8x-1) = 12(3x)
16x-2 = 36x
-2 = 36x-16x
-2 = 20x
-2/20 = x
-1/10 = x
-0.1 = x
_________________________________________________________________

0
The Brainliest Answer!
2014-09-07T23:41:58+05:30
2/3x-1/12=3/2x
grouping x terms together,2/3x-3/2x=1/12
cross multiplying in LHS,4x-9x/6x^2=1/12
-5x/6x^2=1/12.again cross multiplying we get,
=>6x^2=-5x(12)
6x^2=-60x
cancel x on both sides.
so,6x=-60
x=-10 which is the answer.

1 5 1